Bitter Gourd Inhibits the Development of Obesity-Associated Fatty Liver in C57BL/6 Mice Fed a High-Fat Diet. Issue 4 (12th February 2014) - Xu, Jie; Cao, Ke; Li, Yuan; Zou, Xuan; Chen, Cong; Szeto, Ignatius Man-Yau; Dong, Zhizhong; Zhao, Youyou; Shi, Yujie; Wang, Junkuan; Liu, Jiankang; Feng, Zhihui
Abstract: Bitter gourd (BG) is a popular fruit in Asia with numerous well-known medicinal uses, including as an antidiabetic. In the current study, we aimed to explore the effects of BG on mitochondrial function during the development of obesity-associated fatty liver. C57BL/6 mice were divided into 4 experimental groups: mice fed a normal diet (control; included for reference only), mice fed a high-fat diet (HFD), and mice fed an HFD supplemented with freeze-dried BG powder through daily gavage at doses of 0.5 (HFD+0.5BG) and 5 (HFD+5BG) g/kg, respectively. After 16 wk, mice in the HFD+5BG group showed less body and tissue weight gain and less hyperglycemia and hyperlipidemia compared with those in the HFD group ( P < 0.05). In both HFD+0.5BG and HFD+5BG groups, serum interleukin-6 concentration was lower than that in the HFD group ( P < 0.02). The serum C-reactive protein concentration was lower in the HFD+5BG group compared with the HFD group ( P < 0.04). An analysis of liver tissue revealed lower liver triglyceride and cholesterol concentrations in both HFD+0.5BG and HFD+5BG groups than in the HFD group ( P < 0.01). The HFD+5BG group had less activation of the sterol regulatory element binding protein/fatty acid synthase (SREBP-1/FAS) pathway, greater superoxide dismutase activity, and less total protein and mitochondrial protein oxidation than did the HFD group ( P < 0.05). Mitochondrial complex I, II, III, and V activity was greater in the HFD+0.5BG group than in the HFD group ( P < 0.03). The HFD+5BG group only had greater complex V activity compared with the HFD group ( P < 0.05). Mitochondrial dynamics regulators, including dynamin related protein 1 (DRP1) and mitofusin 1 (MFN1), as well as proapoptotic protein expression levels were restored by BG treatment ( P < 0.02). Taken together, our results suggest that BG prevents inflammation and oxidative stress, modulates mitochondrial activity, suppresses apoptosis activation, and inhibits lipid accumulation during the development of fatty liver.